Deficiência de vitamina A e fatores associados em crianças e adolescente em dois municípios do semiárido de Minas Gerais - Romero Alves Teixeira (2010)
The subclinical vitamin A deficiency represents a public health care issue in Brazil and affects over 2 million children. Objectives: to investigate the VAD prevalence and its risk factors in children and adolescents aged from 6 months to 14 years in two counties in the semiarid region of the State of Minas Gerais. Methods: this is a cross- sectional study that involved 719 children in Francisco Badaró (302 agedfrom 6 to 71 months and 417 aged from 6 to 14 years) and 821 children in Novo Cruzeiro (390 aged from 6 to 71 months and 431 from 6 to 14 years), in which the plasma retinol levels and the childrens socioeconomic, demographic, health care, sanitation, food and nutrition security status were assessed. Hemoglobin (direct cianometahemoglobin) C-reactive protein (nephelometry), stool parasitological testing (spontaneous sedimentation), anthropometric measurements and food intake (SFFQ) tests were carried out. The plasma retinol was measured by high performance liquid chromatography and the results interpreted according to theInterdepartmental Committee on Nutrition National Defense (ICNND) criteria. The statistic association between the children characteristics and the plasma retinol levels was assessed by the odds ratio of the logistic regression univaried and multivaried models at the significance level p<0,05. Results: The VAD prevalence among pre-school children was 18,2 and 11,5% in Francisco Badaró and Novo Cruzeiro, respectively. Among the schoolchildren the prevalence was 16,8 and 8,2%, respectively. Among the pre-school children, the VAD was related to: thechilds age, subclinical infection, anthropometric deficit, food and nutritioninsecurity, water supply source, the Program Milk For Life ( Programa Leite pela Vida), geographic region according to the Family Health Strategy (FHS) / Estratégia Saúde da Família (ESF) and the care received from the HSF/ESF teams. Among the schoolchildren, the VAD was related to: the age, subclinical infection, diarrhea, low-fat intake diet, rural area, illiteracy of the person in charge of the child, water supply source, household head unemployment, supplementary feeding program and household crowding. Conclusions: VAD represents a moderate public health issue among preschool children, and among schoolchildren, represents a moderate issue in Francisco Badaro and a mild issuein Novo Cruzeiro. VAD was related to: demographic, socioeconomic, cultural, health care and social programs, morbidity, food insecurity and diet-nutrition factors.